Peran orang tua dalam mendorong motivasi belajar anak - Adzani, Mohamad Adam (Maliki Interdisciplinary Journal, 2024)
Education is an important element in life. Education can be done by teaching. In the process, a child has the right to education. However, nowadays children often do not get the enthusiasm to learn. Due to a lack of understanding and support in the surrounding environment. Children tend to think that school is only a place to play and hang out, so they forget their obligations. On the other hand, parents are also less sensitive to the condition of their children. However, this can be overcome with their awareness. As a parent, of course, you have to support your child’s interests and talents. Meanwhile, a child must be aware of their responsibility to study seriously. With the existence of the role of parents for children to make them motivated and encouraged to be serious